Striking a Balance: A National Assessment of Economic Development Incentives. Issue 3 (May 2021) - Donegan, Mary; Lester, T. William; Lowe, Nichola
The use of incentive packages has intensified as local governments compete for new plants and corporate relocations and as private firms increasingly demand a deal. While incentives promise jobs and tax revenue, scholars and practitioners criticize their high cost and limited accountability. Through a comparison of matched establishments, this article explores how governmental incentive-granting strategy impacts incentive performance. We examine the overall impact of incentives and whether incentives granted to smaller firms perform better. Using economic development budget data, we also assess the state's overall approach to economic development to determine which strategies are prioritized through funding. By showing that incentivized firms fail to create more jobs than matched controls, our analysis casts doubt on claims that "but for" incentives job creation would not occur. Still, our findings suggest that states are smarter in their incentive use when they strike a balance between recruiting industry and supporting "homegrown" businesses and technology.